2001
DOI: 10.1021/jo015618l
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Vinylcarbenoids with Benzaldehydes:  Formation of Vinylcarbonyl Ylides Followed by Ring Closure to Oxiranes and Dihydrofurans

Abstract: Rh(2)(OAc)(4)-catalyzed reaction of vinyldiazo compound 1a in the presence of p-methoxybenz- 2a, mesit- 2b, and p-chlorobenzaldehyde 2c gave a mixture of isomeric vinyloxiranes 3a-c and 4a-c, and sterically unstable (E)-dihydrofurans 5a-c, but not stable (Z)-dihydrofurans 6. However, the reactions with p-nitro- 2d and 2,4-dinitrobenzaldehyde 2e gave (Z)-dihydrofurans 6d,e along with 3d, 4d, and 5d,e. The reaction in the presence of maleic anhydride and dimethyl fumarate gave single 1,3-dipolar cycloadducts 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…The polycyclic systems were obtained and the rhodium catalyst recovered and re-used. In a recent report, Hamaguchi and co-workers [107] showed that both oxiranes (198) and dihydrofurans (199) could be formed nonstereospecifically from vinylcarbonyl ylides (Scheme 32) [108]. On the other hand, Doyle and Timmons reported that phenyldiazoacetate-derived carbonyl and imminium ylides underwent to stereospecific ring closure to form epoxides (201) and aziridines (202), respectively, in high yield (Scheme 31) [109].…”
Section: Heteroannulation Via Ylide Formationmentioning
confidence: 99%
“…The polycyclic systems were obtained and the rhodium catalyst recovered and re-used. In a recent report, Hamaguchi and co-workers [107] showed that both oxiranes (198) and dihydrofurans (199) could be formed nonstereospecifically from vinylcarbonyl ylides (Scheme 32) [108]. On the other hand, Doyle and Timmons reported that phenyldiazoacetate-derived carbonyl and imminium ylides underwent to stereospecific ring closure to form epoxides (201) and aziridines (202), respectively, in high yield (Scheme 31) [109].…”
Section: Heteroannulation Via Ylide Formationmentioning
confidence: 99%
“…Moreover, a formal [6+1] addition reaction to yield dihydrobenzoxepines along with dihydrofurans was reported previously . Afterwards, copper‐catalyzed formal‐[4+1]/[5+1] cyclizations were widely investigated …”
Section: Introductionmentioning
confidence: 99%
“…Given the facility with which these reactions occur and their apparent stereospecificity, we have continued our investigations. Prompted by a recent report that both dihydrofurans and oxiranes are formed nonstereospecifically from vinylcarbonyl ylides (Scheme ), we now report the extension of ylide transformations with styryldiazoacetates to five- and seven-membered ring heterocycles with high or complete stereocontrol
2
…”
mentioning
confidence: 99%